2021
DOI: 10.3389/fphys.2021.751008
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Activated Chloride Channels in Myometrial and Vascular Smooth Muscle

Abstract: In smooth muscle tissues, calcium-activated chloride channels (CaCC) provide the major anionic channel. Opening of these channels leads to chloride efflux and depolarization of the myocyte membrane. In this way, activation of the channels by a rise of intracellular [Ca2+], from a variety of sources, produces increased excitability and can initiate action potentials and contraction or increased tone. We now have a good mechanistic understanding of how the channels are activated and regulated, due to identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 127 publications
(203 reference statements)
0
15
0
Order By: Relevance
“…Since these 2008 reports, many studies have confirmed that TMEM16A generates functional CaCC currents in a number of vascular smooth muscle cells and thereby regulates agonist-induced vasoconstriction [ 21 , 43 , 44 , 45 ]. Moreover, it has been revealed that TMEM16A also contributes to intravascular pressure-induced myogenic depolarization and vasoconstriction in the cerebral arteries and renal arterioles of rats [ 46 , 47 ].…”
Section: Role Of Chloride Ions In Regulation Of Vascular Tone and Blo...mentioning
confidence: 99%
“…Since these 2008 reports, many studies have confirmed that TMEM16A generates functional CaCC currents in a number of vascular smooth muscle cells and thereby regulates agonist-induced vasoconstriction [ 21 , 43 , 44 , 45 ]. Moreover, it has been revealed that TMEM16A also contributes to intravascular pressure-induced myogenic depolarization and vasoconstriction in the cerebral arteries and renal arterioles of rats [ 46 , 47 ].…”
Section: Role Of Chloride Ions In Regulation Of Vascular Tone and Blo...mentioning
confidence: 99%
“…While we did not directly investigate these possibilities, we found changes in urinary norepinephrine were unaltered across all the genotypes examined, which suggest at least sympathetic nerve activity is unaltered by Panx1 in SMCs. The second possibility is that the vasoconstriction may be due to the capacity of Panx1 channels to facilitate anion transport across the plasma membrane, for example, Cl − 25 Although our observation that apyrase reduces EFS constriction suggests a role for extracellular ATP in vasoconstriction, we cannot completely rule out a possible additional contribution of anions such as Cl − , since changes in Cl − are a well-known mechanism to induce SMC vasoconstriction 26 and are worthy of consideration and future study for Panx1 channel activity.…”
Section: Discussionmentioning
confidence: 86%
“…The second possibility is that the vasoconstriction may be due to the capacity of Panx1 channels to facilitate anion transport across the plasma membrane, for example, Cl −25 Although our observation that apyrase reduces EFS constriction suggests a role for extracellular ATP in vasoconstriction, we cannot completely rule out a possible additional contribution of anions such as Cl − , since changes in Cl − are a well-known mechanism to induce SMC vasoconstriction 26 and are worthy of consideration and future study for Panx1 channel activity. How ATP released from SMCs participates in the vascular response to sympathetic nerve stimulation remains to be more thoroughly investigated.…”
Section: Discussionmentioning
confidence: 87%
“…Cl − . 24 Although our observation that apyrase blunts EFS constriction suggests a role for extracellular ATP in vasoconstriction, we cannot completely rule out a possible additional contribution of anions such as Cl − , since changes in Cl − are a well-known mechanism to induce SMC vasoconstriction 25 and are worthy of consideration and future study for Panx1 channel activity.…”
Section: Discussionmentioning
confidence: 87%